2021
DOI: 10.1007/s11606-020-06503-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training and Municipal Support on Primary Health Care–Based Measurement of Alcohol Consumption in Three Latin American Countries: 5-Month Outcome Results of the Quasi-experimental Randomized SCALA Trial

Abstract: Purpose We aimed to test the effects of providing municipal support and training to primary health care providers compared to both training alone and to care as usual on the proportion of adult patients having their alcohol consumption measured. Methods We undertook a quasi-experimental study reporting on a 5-month implementation period in 58 primary health care centres from municipal areas within Bogotá (Colombia), Mexico City (Mexico), and Lima (Peru). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 51 publications
1
21
1
1
Order By: Relevance
“…irrespective of drinking status) was unaffected by either the presence of community support or the intensity of the clinical package, rates were higher amongst those providers who had received training. These latter findings are consistent with our five-month alcohol-related outcome results, where we found that participating in training increased the proportion of patients whose alcohol consumption was measured [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…irrespective of drinking status) was unaffected by either the presence of community support or the intensity of the clinical package, rates were higher amongst those providers who had received training. These latter findings are consistent with our five-month alcohol-related outcome results, where we found that participating in training increased the proportion of patients whose alcohol consumption was measured [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, although training had no direct impact on the proportion of patients with an AUDIT-C score of 8+ assessed for depression, we found an indirect impact of training on the overall proportion of patients assessed for depression. Moreover, as we found non-superiority of the standard package, we conclude that the shorter less intense package can be implemented as the norm [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the international SCALA study, we drew on the model developed by Barker and colleagues (2015) to design and evaluate the impact of supportive actions developed together with local community stakeholders (henceforth: community support) on alcohol measurement in a PHC setting, in three Latin American countries (Jané-Llopis et al, 2020). Interim results are reported elsewhere (Anderson et al, 2021) and show that when analysing changes at the level of the PHC centres (PHCCs), no effects were found of community support on provision of the intervention. A possible reason for the lack of effects was the shorter implementation time of the SCALA project than initially planned (5 months vs. 18 months), due to COVID-19 restrictions.…”
Section: Introductionmentioning
confidence: 99%